Lichens, a unique forage resource threatened by air pollution - Klein, David R.; Vlasova, Tatyana J. (Rangifer, 1992)
Lichens are the primary winter forage for most mainland caribou and reindeer herds in North America and for the majority of domestic and wild reindeer in Siberia and northern Europe, collectively totaling in excess of 5 million animals. Lichens represent a unique forage resource throughout much of the circumpolar North that cannot effectively be replaced by vascular plants. Lichens are particularly sensitive to the effects of air pollution. The increased pace of exploitation and processing of minerals and petroleum resources throughout the circumpolar North, with associated introduction of pollution products into the atmosphere has already resulted in losses of lichens and their reduced productivity in extensive areas adjacent to large metallurgical complexes in the Taimyr of Siberia, on the Kola Peninsula, and in adjacent parts of Finland. Losses of terricolous lichens in the Taimyr from pollution generated by the Norilsk metallurgical complex have been nearly complete within a 300 000 ha area closest to the pollution source and damage and reduced growth extends over an area in excess of 600 000 ha. The Arctic also is a sink for atmospheric pollution generated in the heavily industrialized north temperate regions of the world. Assessment of the effects on lichens of this global scale increase in air pollution is difficult because of the lack of representative controls.